Underrepresentation of Hispanic women in science, technology, engineering, mathematics, and medicine - Jovanka Gencel‐Augusto; Natasha J. Minaya; Daniel E. Johnson; Jennifer R. Grandis (CA: A Cancer Journal for Clinicians, 2025)
Abstract Despite ongoing efforts to increase the number of women in science, technology, engineering, and mathematics (STEM) and in medicine, Hispanic women remain severely underrepresented in these fields. This disparity not only hinders scientific innovation and the delivery of culturally competent medical care but also perpetuates a systemic exclusion. Research specifically addressing the challenges faced by Hispanic women, the extent of underrepresentation in these disciplines, and strategies to mitigate these issues is sparce. The authors conducted a systematic analysis of peer‐reviewed articles to address this gap. The findings reveal a stark underrepresentation of Hispanic women across all examined fields, particularly compared with White women. In addition, the underrepresentation persists when compared with Hispanic men, although the disparity is less pronounced. The authors identify ongoing disparities in promotion, compensation, and retention rates for Hispanic women; present data for barriers to entry and retention; and highlight existing programs and strategies aimed at addressing this underrepresentation. Finally, a framework is presented for future studies and actionable initiatives, and the broader implications of these findings for the field of oncology are highlighted.